Influence of Socio-Demographic Characteristics on Attitude of People towards Mental Health Disorders at Abuja Municipal Area Council - Bello, Umar Lawal; Bilal Bashir Dausayi; Rajah, Amina Sulaiman; Chiroma, Mahmood, Abdulrahman; Declan, Damian; Ugochukwu, Dike Franklin; Oshiorenoya, Dike Sophia; Saidu, Daya Aminu; Eze, Ogechi David (FUDMA Journal of Sciences, 2026)
Mental health disorders represent a growing global public health burden, with Low- and Middle-Income Countries bearing a disproportionate share. In Nigeria, an estimated 20–30% of the population live with some form of mental health disorder. The study aims to determine the influence of sociodemographic characteristics on attitude of people towards mental health disorders at AMC. A community-based descriptive cross-sectional design was employed among 640 adult residents of AMAC aged ≥ 18 years, recruited through multistage sampling. A structured, pre-tested, self-administered questionnaire covering mental health awareness, cultural and religious beliefs, attitudes, stigma, and help-seeking intentions was administered. Data were analysed using SPSS with descriptive and inferential statistics; significance was set at p < 0.05. The mean age of respondents was 51.1 years (SD = 19.1), with a slight female majority (51.6%) and 52.6% having tertiary education. Based on the result, the scores in gender (female: 6.00; male: 5.95) as well as the education levels (primary: 6.15; secondary: 6.00; tertiary: 5.92) and ages showed no statistically significant differences (gender: kh2 = 0.10, p = 0.75; education: kh2 = 1.98, p = 0.37; age: F = 0.26, p = 0.91). In a similar fashion, the scores of attitudes did not differ significantly among all demographic groups, with values that were closed around 0.16 and 0.00. These findings underscore the urgent need for culturally sensitive mental health literacy programmes, strategic engagement with religious leaders, and structural interventions to reduce the financial cost of formal mental health services in AMAC.